141 Evaluation of Use of NABCOP Frailty Score and Interprofessional Variety of WHO Performance Score in Breast Cancer Patients Over 70 Years of Age. (28th February 2022) - Rezacova, M.; Clark, S.
Abstract: Aim: There is requirement to assess frailty of older patients with breast cancer as it can influence practice of treatment. In our department the fitness assessment was inconsistent. Therefore, we have decided to conduct qualitative study to evaluate ease of use of NABCOP frailty score (in comparison with other scales) as well as interprofessional variety of WHO performance score. Method: We have conducted prospective data over 2 weeks period in our busy fast track breast clinic. All new patients over 70 years of age have been identified and asked to perform self-rating assessment. The patient has been later evaluated by NABCOP frailty score and WHO performance score by consultant, nurse, and HCA. This was compared to GP assessment which is part of 2WW referral. Results: There have been matching results between patient's self-assessment, clinician, and HCA in majority of patients. HCA perform assessment well with no discrepancy to other physician. Conclusions: Self-rating and HCA assessment of performance status is accurate and can speed up clinic time. WHO performance scale is found easier and less time consuming by users (and felt provides similar information). We have now provided new assessment system which is undergoing trial in practice at present.